2021
DOI: 10.3389/fphar.2021.793511
|View full text |Cite
|
Sign up to set email alerts
|

Immune Characteristics of IgA Nephropathy With Minimal Change Disease

Abstract: Background: IgA nephropathy (IgAN) has a high degree of heterogeneity in clinical and pathological features. Among all subsets of IgAN, the pathogenesis of IgAN with minimal change disease (MCD-IgAN) remained controversial.Methods: We analyzed the clinical and pathological characteristics of MCD-IgAN patients in a retrospective cohort. Patients diagnosed with IgAN, excluding MCD-IgAN, were randomly selected as controls. Levels of plasma galactose-deficient IgA1 (GdIgA1), IgG autoantibodies against GdIgA1, GdIg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…However, the levels of Gd-IgA1 were much higher in patients with MCD-IgAN than in healthy control participants. Furthermore, unlike previous studies ( 6 , 22 ), we found that Gd-IgA1 was rarely deposited in the glomerulus of patients with MCD-IgAN. Gd-IgA1 was deposited in the glomerulus in only 13.7% of patients with MCD-IgAN, compared with 82.4% of patients with non-MCD-IgAN.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the levels of Gd-IgA1 were much higher in patients with MCD-IgAN than in healthy control participants. Furthermore, unlike previous studies ( 6 , 22 ), we found that Gd-IgA1 was rarely deposited in the glomerulus of patients with MCD-IgAN. Gd-IgA1 was deposited in the glomerulus in only 13.7% of patients with MCD-IgAN, compared with 82.4% of patients with non-MCD-IgAN.…”
Section: Discussioncontrasting
confidence: 99%
“…Gd-IgA1 is the key component in the pathogenesis of IgAN ( 10 ). In this study, we found that, compared with non-MCD-IgAN patients, MCD-IgAN patients presented with lower levels of serum Gd-IgA1, which was consistent with previous research ( 6 ). However, the levels of Gd-IgA1 were much higher in patients with MCD-IgAN than in healthy control participants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease of ALB in IgAN may be due to the renal injury, in accordance with a previous clinical study. 18 The findings suggest that there may not be a remarkable change in the expression level of these genes during the progression of IgAN. Analogously, these hub genes targeted by artemisinin may not have a remarkable expression change against IgAN.…”
Section: Resultsmentioning
confidence: 92%
“…It appears that various environmental factors can stimulate aberrant immunoglobulin-A (IgA) production in areas such as the mucosal-related lymphoid tissue of the alimentary tract, resulting in immune complex deposition in the glomerular structures of the Kidneys (1)(2)(3). Renal biopsy, which is necessary for the definitive diagnosis of IgAN, can result in a range of observations including mild proliferation to significant extra-capillary proliferation of mesangial cells (4). The disease is caused by the dominant mesangial IgA1-immune complex deposits in the mesangial area of the glomeruli (5).…”
Section: Introductionmentioning
confidence: 99%